2022
DOI: 10.3390/ijerph19148434
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Effects of COVID-19 Event Strength on Employee Turnover Intention

Abstract: As a global pandemic, the novel coronavirus (COVID-19) has brought enormous challenges to employees and organizations. Although numerous existing studies have highlighted that the COVID-19 pandemic is a stressful event and empirically proved its detrimental effect on employee turnover intention, few scholars have noted that this pandemic can deteriorate the external economic and employment environment simultaneously, which may further complicate employees’ intentions to leave or stay in the current organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…As a worldwide epidemic, the COVID-19 outbreak, viewed as "a humanitarian crisis" [2], has caused an increased workload on pandemic prevention for most jobs. Recent studies have demonstrated the adverse effect of the spread of COVID-19 on staff's performances, including procrastination, go-slow, and even turnover [3]. For instance, Abdalla [4] found that employee intentions to leave increased due to the COVID-19 crisis.…”
Section: Introductionmentioning
confidence: 99%
“…As a worldwide epidemic, the COVID-19 outbreak, viewed as "a humanitarian crisis" [2], has caused an increased workload on pandemic prevention for most jobs. Recent studies have demonstrated the adverse effect of the spread of COVID-19 on staff's performances, including procrastination, go-slow, and even turnover [3]. For instance, Abdalla [4] found that employee intentions to leave increased due to the COVID-19 crisis.…”
Section: Introductionmentioning
confidence: 99%
“…While there are still many students who face poor on-line higher education conditions, this provides a key foundation for speeding our understanding of accomplishing SDGs in higher education during and after the pandemic, as demonstrated by the findings of (Crawford and Cifuentes-Faura 2022). Deng et al (2022) investigated the impact and strength of the COVID-19 event, which was found to be negatively associated with perceived external employability and, as a result, lowered employee turnover intention. Furthermore, Deng et al observed that organizational identification not only dampened the positive effect of perceived external employability on turnover intention, but also amplified the negative impact of perceived organizational growth on turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…investigated the effect of COVID-19 event strength on the entrepreneurial intentions of college students [30]; Zhou J explored the impact of COVID-19 pandemic strength on work fatigue among policemen [31]; and Deng H et al examined the effects of COVID-19 event strength on employees' turnover intentions [32]. Fewer studies, however, have used the event systems theory to investigate the impact of COVID-19 event strength on the mood and behavior of medical professionals, particularly in the PHC context.…”
Section: Event System Theorymentioning
confidence: 99%